Examination for blood pressure and leg muscle oxygen dynamics during cold water immersion - Takahashi, M. (Japanese Journal of Sciences in Swimming and Water Exercise, 2009)
The purpose of this study was to investigate blood pressure and muscle oxygen dynamics in a rest cold water immersion by using 9 healthy men. The water temperature that we used was 20°C, 25°C, and 30°C in the 15-min-water-immersion tests on sitting posture. As a result, the systolic arterial pressure immediately after immersion was higher than rest value with all conditions. However, only 30°C condition reached a low value after five minutes of the immersion. The diastolic pressure increased by the immersion in 20°C and 25°C condition. On the other hand, diastolic pressure decreased in 30°C condition. Total hemoglobin and deoxy-hemoglobin decreased at the water immersion compared with rest value. In all condition, oxy- hemoglobin was decreased immediately after immersion compared with rest value. There was great difference between 30°C and, 25°C and 20°C, for blood pressure and muscle O2 dynamics. In the conclusion, when the water temperature was 30°C, the cold pressor response was not seen and it was thought that the decreased blood pressure is caused by hydraulic pressure.